Sistem Informasi Pengolahan Data PPKS Pada Sentra Terpadu “Pangudi Luhur” Bekasi - Difa Afnan Ramadhan; Acmad Nurhadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2024)
Integrated center “pangudi Luhur” Bekasi Is an institution that specifically serves the need for social welfare services (PPKS), PPKS is a group, community of people who have obstacles, difficulties, or distractions, unable to carry out their social functions, so they need social services to meet their needs his life both physically and spiritually as well as socially adequately and fairly. Along with the development of technology, PPKS data processing, both registration, progress, and complaints, has not been managed properly in a computerized way, still using paper so that workers really need time to find the PPKS data. So for this reason, a PPKS data processing information system was created to help process PPKS data processing, developments and complaints using a web-based program. The method used in this preparation is the waterfall method. The stages of waterfall development are Analysis, Design, Coding, Unit testing, Maintenance. At this stage of web design using UML, namely: Usecase Diagrams, Squence Diagrams, Class Diagrams, Deployments and ERD. As for the programming support, the Codeigniter Framework is a result of the system being able to provide a web for the integrated “pangudi Luhur” Bekasi center for data processing and PPKS complaints.